Third Five Year Plan 1961-1966 First Year's Programme 1961-1962 Government of Kerala - Planning Commission (Planning Commission, 1961)
The vitiating factors of the State’s economy are the excessive pressure of population on land, chronic shortage in food production, low degree of industrialisation and unemployment, especially in the educated sections of the society. The first year’s programme embodies an endeavour to carry forward the process of curing these basic economic maladies.
Government of Kerala